Epilepsy in children - Wirrell, Elaine (Henry Stewart Talks, 2021)
Incidence of childhood epilepsy, Making a diagnosis of epilepsy, Classification of different epilepsy syndromes, Etiologies of epilepsy, Treatment of childhood epilepsy, Prognosis